Partner turnover and changes in ectomycorrhizal fungal communities during the early life stages of European beech (Fagus sylvatica L.) - Boeraeve, Margaux; Everts, Teun; Vandekerkhove, Kris; De Keersmaeker, Luc; Van de Kerckhove, Peter; Jacquemyn, Hans (Mycorrhiza, 2021)
The first life stages of a tree are subject to strong environmental stresses and competition, limiting their chances of survival. Establishing a mutualistic relationship with mycorrhizal fungi during early life stages may increase growth and survival rates of trees, but how mycorrhizal communities assemble during these stages remains unclear. Here, we studied variation in the ectomycorrhizal (EcM) fungal communities in the soil and roots of Fagus sylvatica seedlings and saplings. Fungal DNA was extracted from the soil and seedling and sapling roots collected in 156 plots across the beech-dominated Sonian forest (Belgium) and community composition was determined through metabarcoding. EcM fungal community composition significantly differed between soil, seedlings and saplings. Russula, Amanita and Inocybe were most abundant in soil, while Lactarius and Scleroderma were more abundant in seedling and sapling roots and Xerocomellus and Laccaria were most abundant in sapling roots. Our results provide evidence of partner turnover in EcM fungal community composition with increasing age in the early life stages of F. sylvatica .